2017
DOI: 10.1007/s13753-017-0151-8
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the El Niño Costero of 2017: The Definition Problem and Challenges of Climate Forecasting and Disaster Responses

Abstract: This preliminary study examines the definition problem and challenges of climate forecasting and disaster responses associated with the El

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 4 publications
1
52
0
1
Order By: Relevance
“…Its duration was much shorter than previous Eastern Pacific El Niño events but SST anomalies and precipitations were nevertheless very intense. As there were no signs of anomalously high temperatures in the equatorial Pacific, the intense coastal warming and its consequences were not anticipated by the local governmental agencies or by the scientific community (Ramirez and Briones, 2017). In the present study, in agreement with Garreaud (2018), we found that the initial warming was mainly associated with a regional decrease of the winds in the far-eastern Pacific.…”
Section: Discussionsupporting
confidence: 91%
“…Its duration was much shorter than previous Eastern Pacific El Niño events but SST anomalies and precipitations were nevertheless very intense. As there were no signs of anomalously high temperatures in the equatorial Pacific, the intense coastal warming and its consequences were not anticipated by the local governmental agencies or by the scientific community (Ramirez and Briones, 2017). In the present study, in agreement with Garreaud (2018), we found that the initial warming was mainly associated with a regional decrease of the winds in the far-eastern Pacific.…”
Section: Discussionsupporting
confidence: 91%
“…In February to April 2017 extremely warm sea surface temperatures (SST) were observed in the far eastern tropical Pacific off Peru and Ecuador, accompanied by heavy rainfalls and flooding over land. The impact on the Peruvian ecosystem and society was comparable to the strong El Niño events of 1982/1983and 1997/1998(Ramírez & Briones, 2017Rodríguez-Morata et al, 2019). Due to its serious impacts, the pronounced warming received a lot of media attention under the term "Coastal El Niño.…”
Section: Introductionmentioning
confidence: 99%
“…For reasons disclosed in the ensuing analysis, the early 2017 floods in Peru were not accompanied by many of the aforementioned atmospheric and oceanic conditions, which inspired us to pursue further exploration. This level of ambiguity in climate forcing compounded the low skill in seasonal forecasting, which hampered decision making (Ramirez and Briones 2017). The objective of this study is to diagnose the Peru floods of 2017 and to examine the possible large-scale forcing.…”
mentioning
confidence: 99%